Persistent storage and query of e-government ontologies in relational databases - Fonou-Dombeu, Jean Vincent; Huisman, Magda; Phiri, Nicholas Mwenya (Springer, 2014)
Over the past eight years, building ontologies for semantic-driven e-government applications has been a subject of interest to e-government researchers. However, only a few has focused on the persistent storage and query of ontologies of the e-government domain. In this paper, 3 selected e-government ontologies are persistently stored and queried in relational databases. The OWL and RDF codes of these ontologies generated with Protégé or downloaded from the Internet are parsed with Jena API (Application Programming Interface) and loaded into MySQL RDBMS (Relational Database Management System). Thereafter, SPARQL queries are written to extract information from the created ontology databases. Experiments show that (1) the Jena parser scales well and could successfully parse and store e-government ontologies of different sizes into relational databases, and (2) the response times of SPARQL queries written in Jena to MySQL ontology databases are proportional to the sizes of the ontologies.
Keywords: E-government; semantic web; ontology storage; ontology query; protégé; Jena API; MySQL; SPARQL